Multiple representations (MR) based instructional approach in support of physics identity and physics teachers' identity development: Design considerations - Nuril Munfaridah; Martin Goedhart (Momentum: Physics Education Journal, 2023)
In this paper, we describe the intervention and the context of implementation of a multiple representations (MR)-based instructional approach as a classroom practice in an first-year thermodynamics course for preservice physics teachers at an Indonesian university. We argue that the implementation of this approach will contribute to the enhancement of students’ conceptual understanding and problem-solving skills. By enhancing those two aspects, we intend to contribute to their development of physics identity and physics teacher identity. We illustrate how this MR approach is applied in the classroom and describe how the relationship between the aspects of this approach interacts with physics identity and physics teacher identity. During lessons the teacher used real-life examples and students were encouraged to use different representations when they solved problems in small groups. The students realized that learning physics could involve many representations and might increase their interest to physics. However, we found some situations that did not match our expectations. For instance, most of the students were more interested when the problems were in the form of mathematical representation. In addition, we found that some students were inactive in the class. Therefore, it is necessary to think as educators about how to provide a positive learning experience to stimulate the development of student's identity. This work exemplifies how physics educators can stimulate physics and physics teacher identity formation in their physics courses as a preparation for future physics teachers.